FREQUENCY OF RECURRENCE OF PARAUMBILICAL HERNIA AFTER MESH REPAIR - REHMAN, SA; ZAHEER, F; ALI, A; IFTIKHAR, HY; FATIMA, SM; KHALID, TBE (Biological and Clinical Sciences Research Journal, 2024)
Para-umbilical hernia is a common abdominal wall defect, and mesh repair is widely used to reduce recurrence rates. However, recurrence remains challenging in clinical practice, especially after elective mesh repair procedures like the Onlay technique. Objective: To determine the frequency of recurrence of para-umbilical hernia following mesh repair using the Onlay technique. Methods: This cross-sectional study was conducted in the Department of Surgery, SMBBMC, Lyari, Karachi, from March 1, 2024, to August 30, 2024, following ethical approval from the institutional review board. A total of 125 patients, aged 18-65 years, were diagnosed with para-umbilical hernia via clinical examination and abdominal ultrasound and undergoing elective mesh repair (Onlay technique) were included through non-probability consecutive sampling. After informed consent was obtained, data on age, BMI, smoking status, diabetes (fasting blood sugar >126 mg/dl or use of antidiabetic drugs), and hernia size (assessed by a consultant radiologist via ultrasound) were documented. Statistical analysis evaluated the recurrence rate and its association with clinical variables. Results: The average age of the participants was 48.68 ± 14.4 years, with a male predominance (55%). The overall recurrence rate following mesh repair was 52%. Stratification of recurrence based on age, gender, BMI, smoking status, and diabetes history revealed no statistically significant associations with the recurrence rate. Conclusion: The recurrence rate of para-umbilical hernia following mesh repair with the Onlay technique was high, at 52%, notably higher than that reported in the existing literature. Further research is needed to identify potential factors contributing to this elevated recurrence rate.